Chronic Pulmonary Aspergillosis as a Considerable Complication in Post-Tuberculosis Lung Disease - Neuböck, Matthias J.; for CPAnet; Günther, Gunar; Barac, Aleksandra; Davidsen, Jesper R.; Laursen, Christian B.; Agarwal, Ritesh; Sehgal, Inderpaul S.; Lange, Christoph; Salzer, Helmut J.F. (Seminars in Respiratory and Critical Care Medicine, 2024)
Post-tuberculosis lung disease (PTLD) has only recently been put in the spotlight as a medical entity. Recent data suggest that up to 50% of tuberculosis (TB) patients are left with PTLD-related impairment after completion of TB treatment. The presence of residual cavities in the lung is the largest risk factor for the development of chronic pulmonary aspergillosis (CPA) globally. Diagnosis of CPA is based on four criteria including a typical radiological pattern, evidence of Aspergillus species, exclusion of alternative diagnosis, and a chronic course of disease. In this manuscript, we provide a narrative review on CPA as a serious complication for patients with PTLD.
Keywords: post-tuberculosis disease; post-tuberculosis lung disease; chronic pulmonary aspergillosis; fungal infection; Aspergillus